Relations and Predicates - Hochberg, Herbert (Philosophische Analyse / Philosophical Analysis, 2004)
Interest in the age-old problems of universals and individuation has received a new impetus from the current revival of ontology in the analytic tradition, the development of theories of individual properties (and the related application of mereological calculi to the analysis of predication), and the particular problems posed by relational predication and the nature of particulars. The essays explore aspects of the history of the issues and attempt to deal with the issues and with challenges to the distinctions that give rise to them. They continue the debates stemming from the revival of metaphysics rooted in Freges realism, the Austrian tradition of Brentano-Husserl-Meinong, and the early 20th century revolt against idealism embodied in writings of Moore and Russell and culminating in Wittgensteins Tractatus.